Laplacian with respect to a measure on a Hilbert space and an L 2-version of the Dirichlet problem for the Poisson equation - Bogdanskii, Yu. V. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
We propose a version of the Laplace operator for functions on a Hilbert space with measure. In terms of this operator, we investigate the Dirichlet problem for the Poisson equation.